2011
DOI: 10.1007/s00216-011-5185-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of a simple gel permeation clean-up procedure coupled to a rapid disequilibrium enzyme-linked immunosorbent assay (ELISA) for the detection of Sudan I dye in spices and sauces

Abstract: Sudan dyes have been found to be added to chilli and chilli products for illegal colour enhancement purposes. Due to the possible carcinogenic effect, they are not authorized to be used in food in the European Union or the USA. However, over the last few years, many products imported from Asian and African countries have been reported via the Rapid Alert System for Food and Feed in the European Union to be contaminated with these dyes. In order to provide fast screening method for the detection of Sudan I (SI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…To date, there have been many methods for the determination of Sudan I, including liquid chromatography (Chailapakul et al, 2008;Qi, Zeng, Wen, Liang, & Zhang, 2011;Qiao, Geng, He, Wu, & Pan, 2011;Xin et al, 2011;Yan et al, 2012;Zhang et al, 2012), capillary electrophoresis (Mejia, Ding, Mora, & Garcia, 2007), immunoassay (Chang et al, 2011;Oplatowska, Stevenson, Schulz, Hartig, & Elliott, 2011;Wang, Yang, Ga, & Deng, 2011), high-resolution 1 H nuclear magnetic resonance spectrometry (Anibal, Ruisánchez, & Callao, 2011), partial filling micellar electrokinetic chromatography (Fukuji, Castro-Puyana, Tavares, & Cifuentes, 2011), and plasmon resonance light scattering (Wu, Li, Huang, & Zhang, 2006). The determination of Sudan I using these techniques shows high sensitivity, but they require expensive instruments, pre-treatment steps, skilled operators, and large quantity of organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been many methods for the determination of Sudan I, including liquid chromatography (Chailapakul et al, 2008;Qi, Zeng, Wen, Liang, & Zhang, 2011;Qiao, Geng, He, Wu, & Pan, 2011;Xin et al, 2011;Yan et al, 2012;Zhang et al, 2012), capillary electrophoresis (Mejia, Ding, Mora, & Garcia, 2007), immunoassay (Chang et al, 2011;Oplatowska, Stevenson, Schulz, Hartig, & Elliott, 2011;Wang, Yang, Ga, & Deng, 2011), high-resolution 1 H nuclear magnetic resonance spectrometry (Anibal, Ruisánchez, & Callao, 2011), partial filling micellar electrokinetic chromatography (Fukuji, Castro-Puyana, Tavares, & Cifuentes, 2011), and plasmon resonance light scattering (Wu, Li, Huang, & Zhang, 2006). The determination of Sudan I using these techniques shows high sensitivity, but they require expensive instruments, pre-treatment steps, skilled operators, and large quantity of organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the authors produced the antibodies against S1 and the obtained antibodies could only detect one (Han et al, 2007;Oplatowska et al, 2011), two (Xu, Wei et al, 2010;Xu, Zhang et al, 2010), three (Ju et al, 2008;Wang et al, 2009) or at most four of the six analytes (Anfossi et al, 2009). The authors of the present paper have produced the antibody against PR for simultaneous determination of the six red dyes (Chang et al, 2011).…”
Section: Introductionmentioning
confidence: 94%
“…There have been some researchers developing ELISA method for the determination of Sudan dyes in various foodstuffs (Anfossi, Baggiani, Giovannoli, & Giraudi, 2009;Chang et al, 2011;Han et al, 2007;Ju, Tang, Fan, & Chen, 2008;Oplatowska, Stevenson, Schulz, & Elloitt, 2011;Wang et al, 2009;Xu, Wei et al, 2010;Xu, Zhang et al, 2010). However, most of the authors produced the antibodies against S1 and the obtained antibodies could only detect one (Han et al, 2007;Oplatowska et al, 2011), two (Xu, Wei et al, 2010;Xu, Zhang et al, 2010), three (Ju et al, 2008;Wang et al, 2009) or at most four of the six analytes (Anfossi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it was demonstrated that immunosorbent assays [18][19][20][21] as well as electrochemical sensors based on voltammetric readout [22][23][24] can be applied for this analytical problem. Additionally, the applicability of nuclear magnetic resonance (NMR) spectroscopy in combination with chemometric methods was presented [25,26].…”
Section: Introductionmentioning
confidence: 99%